METODE KLASIFIKASI DATA MINING ALGORITMA C4.5 DAN PART UNTUK PREDIKSI WAKTU KELULUSAN MAHASISWA DI UNIVERSITAS DARWAN ALI - Selviana Yunita; Nurahman Nurahman (Informasi Interaktif, 2022)
College is one of the most influental education aspect for a nation’s improvement. The quality of a college is important to support and explore student potential. The quality of a college helps student to prepare theirselves in working world. One of the qualities of a college can be seen from the punctuality of graduating time for students. It is become important for a college to find out the factors that influence the punctuality of graduating time for students. Darwan Ali University is one of university located in Sampit, Central Kalimantan. Based on their Information System Management, in 2011, there are 707 new students. In 2015 only 290 students passed. It shows that only 41% of students graduate on time. The source of this research data comes from Management Information System of Darwan Ali University. The purpose of this research is to find the rules which affects the accuracy of student graduation. The data used in this study include departement of study programs, the GPA from first to fourth semester, and gender of students. This study uses two algorithms, namely the C4.5 and PART algorithms. The researcher also found that the C4.5 algorithm has better accuracy than PART, with an accuracy level of 83.004 %. Keywords: Classification, data mining, C4.5, PART